Biomedical applications of functionalized nanomaterials : concepts, development and clinical translation - Sarmento, Bruno; Neves, Jose das, 1978- (Micro & nano technologies., 2018)
Biomedical Applications of Functionalized Nanomaterials: Concepts, Development and Clinical Translation presents a concise overview of the most promising nanomaterials functionalized with ligands for biomedical applications. The first section focuses on current strategies for identifying biological targets and screening of ligand to optimize anchoring to nanomaterials, providing the foundation for the remaining parts. Section Two covers specific applications of functionalized nanomaterials in therapy and diagnostics, highlighting current practice and addressing major challenges, in particular, case studies of successfully developed and marketed functionalized nanomaterials. The final section focuses on regulatory issues and clinical translation, providing a legal framework for their use in biomedicine. This book is an important reference source for worldwide drug and medical devices policymakers, biomaterials scientists and regulatory bodies.